Peningkatan Kompetensi IT Pemuda Patitech Academy Melalui Pelatihan Perakitan, Instalasi, dan Troubleshooting Komputer (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The development of the digital era demands that youth possess practical and applicable information technology (IT) skills to enhance competitiveness in the workforce and entrepreneurship. However, the gap between theoretical knowledge and basic technical skills—such as computer assembly, installation, and troubleshooting—remains a real challenge among youth, particularly in community settings such as the Patitech Academy in Pati Regency. The training program was implemented using experiential learning methods and a participatory approach over three days. A total of 25 participants engaged in a series of activities, including socialization, technical training, intensive mentoring, and evaluation. Measurement instruments included written pre- and post-tests, practical performance observation, and satisfaction questionnaires. Data analysis showed a significant improvement in participant competencies. The average post-test score increased by 40.2% compared to the pre-test, with 85% of participants demonstrating mastery in assembling computers, installing operating systems, and performing basic troubleshooting independently. The troubleshooting aspect recorded the highest increase (45%). The success of the program was supported by direct learning methods, an ideal participant-instructor ratio, and a curriculum relevant to industry needs. Hands-on training proved effective in significantly improving youth technical IT competencies. The program not only built hard skills but also increased participants' self-confidence and independence. For sustainability, it is recommended to develop advanced modules, strengthen industry networking, and establish a digital alumni forum. The findings of this study can serve as a model for developing youth empowerment programs based on digital skills in other communities.